Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Perusahaan Food and Beverages Yang Listing di Bursa Efek Indonesia (BEI) Tahun 2009 – 2012 - Putera, Fauzan Adha; Hasan, Mudrika Alamsyah; ', Zirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The principal purpose of this study was to investigate the association between the efficiency of Value Added Intellectual Coefficient (VAIC™) by the major components of a firm’s resources base (physical capital, human capital, and structural capital) and traditional of financial company performance Return On Assets (ROA). Data were drawn from 12 Indonesian food and beverages sectors were listed in BEI for four years, 2009 – 2012. It was an empirical study using return on assets (ROA) for the data analysis. Result of this research indicate the existence of a significant positive relationship between intellectual capital (VAIC™) with financial company’s performance. The empirical findings show that physical capital (VACA), human capital (VAHU), and structural capital (STVA) have significant positive relationship with the companies activity of companies listed on the Indonesia Stock Exchange Exchange in the four years observation.Keywords: Intellectual Capital (VAIC™), Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), and Return on Assets (ROA).